Ecotourism in Valea Vaserului - Radu Otilia (Ovidius University Annals: Economic Sciences Series, 2018)
Throughout this paper we study the eight principles of ecotourism by combining the theory with the observations made at the site, in Valea Vaserului, during two years, 2017 and 2018, which had a major impact on the increase of tourism and especially ecotourism on the local level. Each of these principles is analyzed in the light of the details observed at the site and it is demonstrated that in this area they are fully applied and ecotourism turns from tourism for a small number of tourists into mass tourism, mass ecotourism. By combining economic achievements with people's desire to visit and preserve nature, ecotourism is one of the most important directions of tourism development. As a consequence, we need to create more areas similar to the one we are studying in this article, which is an example of good practice in ecotourism.